From Natural Rubber to Smart Surfaces - Sureurg KHONGTONG (Walailak Journal of Science and Technology, 2011)
Surface oxidation of crosslinked natural rubber provided a hydrophilic substrate that reconstructed under nitrogen atmosphere at room temperature to become more hydrophobic. Subsequent equilibration against water at room temperature returned its original hydrophilicity. This behavior may arise from the minimization of interfacial free energy of the system by the migration of hydrophilic functional groups away from or to the interface. The change in surface moieties, influences tackiness at the rubber surface - it is tackier when functional groups are at the interface rather than when they migrate away. The magnitudes and kinetics of this surface reconstruction depends on the molecular weight between crosslinks (Mc) and temperature. The results reported here provide information for further development of smart surfaces from crosslinked natural rubber.